Diabetic Heart Disease (British Journal of Multidisciplinary and Advanced Studies, 2023)
Changes in the human environment, behavior, and lifestyle are contributing to the upsurge in the incidence of diabetes. However, better management has resulted in a longer survival of patients with diabetes, but it is accompanied by long-term chronic complications due to hyperglycemia. Individuals with diabetes most often die of cardiovascular disease (CVD) rather than from a cause uniquely related to diabetes, such as ketoacidosis or hypoglycemia. Diabetic patients have a twofold to six-fold higher incidence of cardiovascular disease than nondiabetic population. Furthermore, diabetic patients with CVD sustain a worse prognosis for survival than CVD patients without diabetes and their quality of life also depreciates. Therefore, diabetes has been considered as having a risk equivalent to a nondiabetic patient with preexisting heart disease. Identification of patients at risk for CVD could felicitate the prevention or retardation of cardiovascular events. The management of CVD prevention and the problem associated with it needs intensified monitoring by pharmacist.